Analysis of Foreign Trade and Its Economic Impact on the Countries of Central Asia - Wei Tong; T. B. Urzhumtseva (Евразийская интеграция: экономика, право, политика)
The study of cooperation between Central Asian countries in foreign trade is topical due to the role of foreign trade as an important factor in the economic growth of Tajikistan, Uzbekistan, Kazakhstan, Turkmenistan and Kyrgyzstan. Foreign trade is an important tool of the Central Asian countries’ integration into the world economy and is of key importance for the future development of the national economies of all countries. The article analyzes the volume of Central Asian countries’ foreign trade for the period 2000–2016, the economic impact of foreign trade on their development. Despite the entry into force of the EAEU customs code, one of the objectives of which was to strengthen the foundations of the common commodity market, the share of EAEU foreign trade currently significantly exceeds the share of domestic trade, which is a weak point in the process of domestic economic integration. The challenge is still to reduce the region's dependence on the international market.